Virtual Influencers : Is The Persona Trustworthy? - Rafki Chandra Wibawa; Chairani Putri Pratiwi; Eko Wahyono; Desman Hidayat; Wilyan Adiasari (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2022)
In today's digital world, people are using social media at a higher rate than ever before. One digital marketing phenomenon is the use of services from a virtual influencer. Virtual influencers are computer-generated models who are becoming increasingly famous on social media. The purpose of the study is to identify and analyze the communication way of virtual influencers in the digital marketing era. The current study uses a literature review method that searches article titles and abstracts in electronic databases (Scopus and Google Scholar) for studies published between 2018-2022 using keywords. The importance of this research is due to the phenomenon and data literature on lifestyle, interaction patterns, and most of the media production from conventional to digital which has a significant impact on the development of the digital world. The results show the perspective of digital experts on the efficacy and trustworthiness of the use of virtual influencers as a marketing strategy is capable of promoting businesses. Virtual characters can give a new color and dimension to the global marketing world and will be widely used in various industries such as fashion, music, games, films, marketing, education, and politics.